2001
DOI: 10.1159/000049957
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Germ Cell Development in Cryptorchidism

Abstract: Background: Previous studies suggest that two fundamental, probably androgen-dependent, steps in maturation of germ cells normally occur in the prepubertal testis: the disappearance of gonocytes (the fetal stem cell pool) and the appearance of adult dark spermatogonia (the adult stem cell pool) at 2–3 months of age and the appearance of primary spermatocytes (the onset of meiosis) at 4–5 years. Previous studies of small series of cryptorchid boys suggest that both steps are defective in undescended testes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 16 publications
7
100
0
6
Order By: Relevance
“…At a recent examination at an average age of 19 years (95% CI [18][19][20][21][22], all males were in a healthy condition. They all had Tanner V stage of sexual development and normal erectile function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a recent examination at an average age of 19 years (95% CI [18][19][20][21][22], all males were in a healthy condition. They all had Tanner V stage of sexual development and normal erectile function.…”
Section: Resultsmentioning
confidence: 99%
“…This insufficient testosterone secretion is responsible for impaired transformation of gonocytes into Ad spermatogonia (4,5,11,(15)(16)(17). Additional rationale for LH-RHa treatment was based on the histological analyses of undescended testes in infancy (4,5,11,(15)(16)(17)(18)(19)(20). ment of impaired mini-puberty should be performed before this age.…”
Section: Commentsmentioning
confidence: 99%
“…Treatment timing has been based on the knowledge that delay and defect in the pre-pubertal maturation of germ cells is associated with a reduction in the number of germ cells in cryptorchidism 23 . Pre-pubertal treatment with hormones could, theoretically, achieve a normal maturation and proliferation of germ cells by increasing the total number of these cells and improving the fertility rates 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Other evidences collected over the years have indicated that increased testicular temperature negatively influences the development and differentiation of Leydig cells causing impairments in sex hormones biosynthesis (Huff et al, 2001;Kotula-Balak et al, 2001;Pinart et al, 2000).…”
Section: Temperature and 3β-hsd Activitymentioning
confidence: 99%